Present vs. Future Property Losses From a 100-Year Coastal Flood: A Case Study of Grand Isle, Louisiana - Mostafiz, Rubayet Bin; Bushra, Nazla; Rohli, Robert V.; Friedland, Carol J.; Rahim, Md Adilur (Frontiers in Water, 2021)
Louisiana, U.S.A., is among the world's most vulnerable places to coastal flooding. Increasing frequency/intensity of natural hazards under climate change scenarios is expected to exacerbate Louisiana's coastal flood risk. Although many factors are involved, land subsidence from marshland compaction and underground resource extraction, shoreline erosion accelerated by eustatic sea level rise (ESLR), and tropical-cyclone-induced storm surge are among the most important. While past research has focused on flood risk assessment and mitigation strategies, including climate change scenarios, few studies examine all of these factors collectively. This study shows present pluvial flood depth and the contributions of additional coastal subsidence and ESLR toward future (2050) pluvial flooding. Then, current tropical-storm-induced storm surge and future storm surge depth modeled by Louisiana's Coastal Protection and Restoration Authority (CPRA) under climate change scenarios are presented. Present and future 100-year pluvial flood and storm surge losses (separately, 2020$) to structures and their contents are estimated at the individual building level for Grand Isle, Louisiana, a barrier island town of ecological, economic, historical, recreational, cultural, and aesthetic treasure. Results suggest that the average 100-year pluvial flood depth in buildings will increase by 1.35 feet by 2050, with subsidence contributing over 82% of this total. Subsidence is projected to escalate structure and content losses by ~17% above losses in 2017, while ESLR may contribute ~3% above 2017 losses. A 100-year tropical-cyclone-induced storm surge event amid a “low” scenario of environmental change as defined by CPRA would increase Grand Isle's structure and content losses by 68–74% above the 2017 value by 2027, 141–149% by 2042, and 346–359% by 2067. The (“high”) scenario of environmental change would increase the 100-year storm surge losses by 85–91% above the 2017 value by 2027, 199–218% by 2042, and 407–415% by 2067. Outcomes from this study will offer a more realistic risk assessment model and will direct flood risk managers, property owners, and other stakeholders to build a comprehensive framework to minimize future flood risk in one of the most vulnerable sites in the U.S.A. to coastal flooding.